On the advantage of being left-handed in volleyball: further evidence of the specificity of skilled visual perception - Loffing, F.; Schorer, J.; Hagemann, N.; Baker, J. (Attention, Perception, & Psychophysics, 2012)
High ball speeds and close distances between competitors require athletes in interactive sports to correctly anticipate an opponent`s intentions in order to render appropriate reactions. Although it is considered crucial for successful performance, such skill appears impaired when athletes are confronted with a left-handed opponent, possibly because of athletes` reduced perceptual familiarity with rarely encountered left-handed actions. To test this negative perceptual frequency effect hypothesis, we invited 18 skilled and 18 novice volleyball players to predict shot directions of left- and right-handed attacks in a video-based visual anticipation task. In accordance with our predictions, and with recent reports on laterality differences in visual perception, the outcome of left-handed actions was significantly less accurately predicted than the outcome of right-handed attacks. In addition, this left-right bias was most distinct when predictions had to be based on preimpact (i.e., before hand-ball contact) kinematic cues, and skilled players were generally more affected by the opponents` handedness than were novices. The study`s findings corroborate the assumption that skilled visual perception is attuned to more frequently encountered actions.